Interdisciplinary Dentofacial Therapy: Maximizing Diagnosis and Treatment in Oral Health - Kashif Adnan, Muhammad Ahsan Fayyaz, Permanand, Naresh Kumar, Shahrukh Irfan, Avinash (Pakistan Journal of Medical & Health Sciences, 2023)
Aims: This study aims to investigate the current practices of Interdisciplinary Dentofacial Therapy (IDT) in the detection and management of prevalent oral illnesses. In order to ascertain the significance of Interdisciplinary Dentofacial Therapy (IDT) in optimizing preventative oral health, a comprehensive analysis is required. Method: For this purpose, the study's approaches were centered on investigating the current practices of interdisciplinary dentofacial therapy (IDT) in relation to oral health. The researchers aimed to explore the potential benefits of integrating various dental specialties and their collaboration in treating complex oral health issues. They also examined the impact of IDT on patient outcomes, such as improved treatment outcomes, enhanced patient satisfaction, and reduced treatment time. This cross-sectional survey was conducted during the period of March 2023 across the world. The purpose of the survey was to gather data on various socio-economic factors and their impact on global trends. Participants were selected randomly from diverse demographics to ensure a representative sample. The research focused on a global sample of orthodontists, oral surgeons, and ear-nose and throat (ENT) specialists. Results: This study elucidates the deficiencies in interdisciplinary oral health care and identifies the factors that impact four distinct cohorts of healthcare providers. The findings of our study indicate that certain criteria, namely professionals (Orthodontics or Oral Surgeons) and years of experience (more than 3 years), were found to be positively correlated with increased likelihood of referral practices. Practical Implications: Among the characteristics that contribute to the facilitation of multidisciplinary activities, it was shown that the source of oral health knowledge, specifically from the Ministry of Health (MOH) and formal education, was substantially associated with increased likelihood of engaging in such practices. Conclusion: The current study demonstrated that interdisciplinary dentofacial therapy is feasible if all oral health professionals collaborate. In addition, the investigation revealed disparities between healthcare professionals' interdisciplinary dentofacial therapy (IDT) knowledge and attitudes. The implementation of interdisciplinary dentofacial therapy (IDT) varied among healthcare professionals. Recognizing the importance of the disparity in oral health education, it is essential to implement comprehensive professional training in undergraduate and graduate programs. Keywords: Interdisciplinary Dentofacial Therapy, Oral health